High‐fat diet during adulthood interacts with prenatal stress, affecting both brain inflammatory and neuroendocrine markers in male rats. (26th March 2021) - Berry, Alessandra; Mazzelli, Monica; Musillo, Chiara; Riva, Marco Andrea; Cattaneo, Annamaria; Cirulli, Francesca
Abstract: Prenatal stress (PNS) affects foetal programming and, through an interaction with subsequent challenges, can increase vulnerability to mood and metabolic disorders. We have previously shown that, following PNS, adult male rats are characterized by increased vulnerability to a metabolic stressor experienced at adulthood (8‐week‐high‐fat diet—HFD). In this study, we specifically assessed whether PNS might interact with an adult metabolic challenge to induce an inflammatory phenotype. Changes in the expression levels of inflammatory ( Il‐1β, Tnf‐α, Il‐6 ) and of stress response mediators ( Nr3c1, Fkbp5 ) as well as of mood and metabolic regulators ( Bdnf, Ghs‐R ) were investigated in the hippocampus, prefrontal cortex and hypothalamus, brain regions involved in the pathogenesis of depression and prone to inflammation in response to stress. Overall, PNS reduced the expression of Bdnf and Tnf‐α, while HFD administered at adulthood counteracted this effect suggesting that PNS impinges upon the same pathways regulating responses to a metabolic challenge at adulthood. Furthermore, HFD and PNS affected the expression of both Nr3c1 and Fkbp5, two neuroendocrine mediators involved in the response to stress, metabolic challenges and in the modulation of the emotional profile (as shown by the correlation between Fkbp5 and the time spent in the open arms of the elevated plus‐maze). Overall, these results indicate that the same metabolic and neuroendocrine effectors engaged by PNS are affected by metabolic challenges at adulthood, providing some mechanistic insight into the well‐known comorbidity between mood and metabolic disorders. Abstract : Based on the "two hit model" of the developmental origin of diseases, PNS (first hit) affects foetal brain developmental trajectories; signalling pathways related to brain plasticity and function ( Bdnf, Tnf‐α and Il‐β ) are down‐set potentially providing increased liability to later‐life mood and metabolic disorders particularly in male offspring. A later‐life challenge such as HFD feeding (second hit), experienced at adulthood, might impinge upon the same signalling pathways primed by PNS leading to enhanced responses to the metabolic challenge. The hippocampus and prefrontal cortex, being main targets of glucocorticoids, are finely modulated by PNS and readily respond to the HFD metabolic stress.